Abnormal returns and idiosyncratic volatility puzzle: An empirical investigation in Vietnam stock market - Xuan Vinh Vo; Van Phong Vo; Thanh Phuc Nguyen (Cogent Economics & Finance, 2020)
This paper aims to examine the relation between idiosyncratic volatility (IVOL) and stock returns with full-sample and conditional alpha sub-samples in Vietnam stock market covering the period from January 2008 to December 2018. We test the IVOL effect on stock returns employing Fama-Macbeth regression method (firm-level analysis) and sorting portfolio method (portfolio-level analysis). In addition, we use different approaches to estimate IVOLs which are the standard deviation of the residuals estimated from regression based on capital asset pricing model (CAPM), Fama-French three-factor model and Carhart four-factor model. We find the IVOL effect which is considered as IVOL puzzle in positive alpha sub-samples. However, we do not discover any significant relation in full-sample and negative alpha sub-samples. Besides, these findings are not consistent with prospect theory. This paper also suggests IVOL opposite strategy for investors to generate significant returns by collecting stocks in positive alpha sub-samples.
Keywords: G02; G12; G14; 330; abnormal returns; asset pricing; idiosyncratic volatility